Research Methodology : The Aims, Practices and Ethics of Science - Pruzan, Peter (2016)
This book is an in-depth guide to effective scientific research. Ranging from the philosophical to the practical, it explains at the outset what science can - and can't - achieve, and discusses its relationship to mathematics and laws. The author then pays extensive attention to the scientific method, including experimental design, verification, uncertainty and statistics. A major aim of the book is to help young scientists reflect upon the deeper aims of their work and make the best use of their talents in contributing to progress. To this end, it also includes sections on planning research, on presenting one's findings in writing, as well as on ethics and the responsibilities of scientists.
Introduction -- Science -- Hypotheses, Theories and Laws -- Scientific Statements: Their Justification and Acceptance -- Measurement -- Experimentation -- Scientific Method and the Design of Research -- Uncertainty, Probability and Statistics in Research -- Research -- Ethics and Responsibility in Scientific Research.
Keywords: Measurement; Physical measurements; Research-Moral and ethical aspects; Science education; Sociology -- Research; Statistics; Measurement Science and Instrumentation; Research Ethics; Research Methodology; Science Education; Statistics for Life Sciences, Medicine, Health Sciences